Comparative study on the use of antioxidants rich vegetables and first evidence of carotenoids and phenolic compounds from fresh carrot as natural antioxidants to stabilize lipid in highly fatty hilsa shad (Tenualosa ilisha) - Akter Mousumi; A.K.M. Alam Nowsad; Md. Ismail Hossain; Al Shahriar (Applied Food Research)
Natural antioxidants from vegetable sources that are suitable to use in hilsa products was searched to stabilize its lipids to keep original flavors. Carrot, tomato and pumpkin treated products were prepared and their suitability and antioxidant capability were evaluated by evaluating sensory and biochemical characteristics. The lower PV and TBARS values found in the carrot-treated hilsa cubes than other two might indicate that the carrot used in hilsa cube had strong anti-oxidative properties. The antioxidant activity tests of the carrot extract were carried out in detail indicated that carrot contained a significant amount of antioxidant phenolics, flavonoids and beta-carotene. Effectiveness was also compared with synthetic antioxidant (BHA). It was concluded that carrots could be used as a source of natural antioxidant to stabilize lipids in highly fatty hilsa fish. A probabilistic pathway of phytochemicals from fresh carrot to scavenge free radicals and prevent oxidation of hilsa oil has been suggested.